Élaboration et premiers pas de validation de questionnaires pour évaluer la fidélité du modèle de réponse à l’intervention en littératie dans les écoles primaires francophones québécoises - Demers, Catrine; Moreau, André C.; Lefebvre, Pascal (Canadian Journal of Education/Revue canadienne de l'éducation, 2020)
Many French-speaking elementary schools in Quebec implementing the Response to Intervention (RTI) model in literacy need to evaluate the accuracy (or fidelity) of its implementation. In collaboration with schools, this study is aimed at developing and validating instruments to evaluate the fidelity of RTI and its implementation strategies. Self-evaluation questionnaires were developed, including the completion of group meetings with 50 participants to adapt the content to the context and cognitive interviews with 35 participants to pretest the questionnaires. These questionnaires will help inform feedback on the implementation of RTI, and are essential to evaluate the efficacy of RTI. Keywords: response to intervention, fidelity, implementation, reading, writing, literacy, questionnaires, validity